Effect on Foliar Feeding of Plant Growth Regulators and Micronutrients on Flowering attributes of Ber (Ziziphus mauritiana Lamk) fruits cv. Gola - Brijesh Patel; Bhagwan Deen (The Bioscan, 2026)
The study was carried out on six-year-old Ber (Ziziphus mauritiana Lamk.) trees cultivated under sodic soil conditions at the Production Processing of Fruits and User Waste Land, Akma. The research was undertaken within the Department of Fruit Science, College of Horticulture and Forestry, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya (U.P.), during the academic years 2023–24 and 2024–25. The objective of the investigation was to evaluate the impact of foliar application of plant growth regulators and micronutrients on fruiting character of Ber cv. Gola fruits. The experiment was laid out in a RBD (Randomized Block Design) and data were collected on key preharvest parameters including Flowering initiation time, Number of flowers per shoot, Days taken to 50 % flowering, Days taken for full bloom. Among the treatments, T12 (GA₃ 20 ppm + NAA 30 ppm + ZnSO₄ 0.5% + Borax 0.5%) consistently minimized the time required for flowering initiation, increased the number of flowers per shoot, and reduced the days taken to reach 50% flowering as well as full bloom, across both years and in the pooled mean, compared with the control. Keywords Ber, Randomized Block Design, Flower and Boran